A model of allocation, negotiation and redistribution of resources, based on intelligent agents - Véliz Quintero, Eduardo; Jiménez Mosquera, Carlos (ACI Avances en Ciencias e Ingenierías, 2014)
The present work is an application of artificial intelligence, based on intelligent agents, to simulate the allocation, negotiation and redistribution of financial resources by Central Government to autonomous decentralized municipal governments. The goal is to develop a model based on intelligent agents using Netlogo, that allow the distribution of resources to autonomous decentralized municipal governments based on social variables such as deficit of housing, access to services and/or poverty by unsatisfied basic needs.